Introduction to electronic components in web site for electrical engineering laboratory / Nazrulazhar Bahaman - Bahaman, Nazrulazhar (1998)
This project explores the development of a web application using Java Language, Java Script and HTML (hyper text markup language). The web application is a computer aided learning (CAL) package that attempts to introduce students to electronic components. On running the application, students (users) can learn from online notes or choose to learn from the other features of the application which includes computation of resistance value, decimal number conversion and animated electronic components operation. By specifying inputs to various types of gates, an animated presentation of how the gates function can be witnessed. They can also attempt a simple quiz at the end of the presentation. The comments and suggestion site give a chance to reply back any question in on line system.